Blended Learning with Science-Technology-Society Approachment: A Literature Review - Huda, Nuril; Mustaji Mustaji; Fajar Arianto (Open Access Indonesia Journal of Social Sciences, 2021)
One of the efforts made so that humans are able and able to develop their potential is through a learning process. Blended learning encourages students to be more active and increases independence in learning. Students are required to learn and access material independently, and complete assignments given by the teacher, both individually and in groups. This literature review aims to discuss strategies for implementing blended learning as a student learning method. With the development of science and technology which is increasingly rapid, nowadays it has a lot to affect human life so that it can have a positive impact, namely improving the quality of life and making human work easier. The negative impact is that it can cause changes in the values, norms, rules, or morals of life adopted by the community. Therefore we need people who are able to think critically, creatively, logically and take the initiative in responding to issues in society that are caused by the impact of the development of science and technology, especially in the world of education.